Response surface methodology approach for adsorptive removal of Reactive Blue 19 onto green pea pod - Demirhan, Elcin (IWA PUBLISHING, 2020)
In the present study, removal of Reactive Blue 19 dye by using green pea pod as a low-cost adsorbent was investigated. Box-Behnken design was used to determine the independent and interaction influences of process variables of pH, temperature and adsorbent amount. The variance analysis (ANOVA) results showed that the second order model with high coefficient of determination value (R-2= 0.9997) was statistically significant. The experimental results stated that the removal efficiency increased when the pH value decreased and the adsorbent amount increased. The maximum removal (99.42%) was obtained at pH 2, temperature of 35 degrees C and adsorbent amount of 1.5 g/100 mL. The equilibrium data investigation showed that the Freundlich isotherm model fitted better for removal of dye than did the Langmuir isotherm model. Furthermore, the adsorption kinetic was also evaluated and it was found that the adsorption followed the pseudo second order model for the Reactive Blue 19 removal onto green pea pod.
Keywords: adsorption; anionic dye; Box-Behnken design; isotherm; kinetic; low-cost adsorbent; WASTE-WATER; AQUEOUS-SOLUTIONS; METHYLENE-BLUE; LIGNOCELLULOSIC WASTE; PROCESS OPTIMIZATION; MALACHITE GREEN; DYE; EQUILIBRIUM; BIOSORBENT; PEEL; Engineering; Environmental Sciences & Ecology; Water Resources